APPLICATION OF FUZZY LOGIC TO CONTROL TECHNOLOGICAL PARAMETERS IN THE METERING UNIT (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article discusses the issues of creating an algorithm for controlling the technological parameters of a gas pipeline - pressure and gas flow using a fuzzy PID controller, the relevance of solving the problem of creating automatic control systems using intelligent control automation technologies and monitoring technological parameters. According to the author's conclusion, the use of a control algorithm based on fuzzy logic makes it possible to better adapt to the variable operating mode of the gas pipeline and does not require constant selection of the PID controller coefficients.